SOCIAL CONFLICT IN THE NOVEL “DAD” THE WORK OF ANDREA HIRATA; LITERATURE SOCIOLOGY OVERVIEW - Liga Febrina; Hasmi Novianti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
Literary works are something produced by humans, using language to produce aesthetic value. However, in this case, the author creates literary works not merely carve the aesthetic value but to produce a message or virtue values. Through literary works, one can express his or her view of life around him. One of the literary works is the novel. The novel used in this research is Andrea Hirata's father's novel. This novel provides an overview of social conflicts that often occur in the community and among teenagers. In addition to describing social conflicts, Andrea Hirata's novel's dad is relevant to today's life that can later be used as real life learning.This type of research is a literary research using hermeneutic methods, which is trying to understand the meaning of literature that lies behind the structure. Understanding the meaning, not only on the symbol, but rather view literature as text. The object of this research is Andrea Hirata's father's novel. Data collection techniques used by researchers is to read and understand the entire contents of the novel, marking data and record data in accordance with social conflict figures. Data analysis technique in this research is identification, data classification, interpretation, and interference.Based on the results of research done on the novel Ayah by Andrea Hirata, it can be concluded that there are 10 data, with the division as follows: personal contradictions that occur between individuals in the social environment there are 9 data, and the contradiction between social classes caused by the difference of interests between superiors with subordinates, there is 1 data. Based on these data, it can be interpreted that there are two forms of social conflict contained in the novel Ayah by Andrea Hirata that can be used as learning for researchers and for readers to be represented in real life.